Dynamics of endothelial function violation in patients with arterial hypertension with moderate cardiovascular risk and antihypertensive therapy treatment influence - T. S. Turlyun (Zaporožskij Medicinskij Žurnal)
Aim. To assess the impact of one-year monitored different groups’ antihypertensive therapy on markers of endothelial dysfunction.